Needs Assessment: Concepts and Two Approaches - Medina Díaz, María (2025)
This article discusses the concept of needs and examines two approaches to needs assessment in the educational field. Its purpose is to present different perspectives on needs assessment in order to foster discussion and research among those interested in the topic.